UPAYA PEMERINTAH LOKAL PADA MASA PANDEMI COVID-19 DALAM BIDANG SOSIAL MASYARAKAT DI KOTA TEBING TINGGI PROVINSI SUMATERA UTARA - Natalia Syafitri Br. Marpaung; Adelina Sri Mustika Br Bangun; Andre Genesa Harahap (Communicative : Jurnal Dakwah dan Komunikasi, 2023)
This research focuses on the mayor's regulation (perwal) No 44 of 2020, namely article 9 sanctions and article 10 socialization and participation. Therefore, this research aims to find out the local government's efforts in the social field of society during the Covid-19 pandemic in Tebing Tinggi city. This research uses qualitative research with a case study method. The results obtained are the Covid-19 Task Force of the Komifo Service as the coordinator of the socialization and participation field has made many activities which are divided into two directions, first going directly to the field, namely mobile broadcasts and holding socialization, then using many media such as mass media and social media. Furthermore, the Covid-19 Satpol PP Task Force as the coordinator of the field of sanctions in applying social sanctions such as sweeping the streets, pushing up five to ten times, singing national songs, and mentioning the points of Pancasila. All policies that are implemented in general are not found obstacles, but the social sanctions are not enough to provide a deterrent effect compared to administrative sanctions